The Use of Analogies by Future Physics Teachers in Conducting Supervised Internship Activities - Parma, Fabiano Willian [UNESP]; Vieira, Murilo Henrique Alfredo [UNESP]; Nardi, Roberto [UNESP] (The University of Sydney Library, 2024)
Analogies are frequently used in people's daily lives to relate unfamiliar domain knowledge to everyday knowledge. Because analogies are so common to humanity, using them in teaching and learning is effective for helping students better understand abstract material. In this way, in a supervised internship, we sought to investigate how future physics teachers used analogies during a mini-course on Thermology. Classes were held in two school centres from different contexts: a youth and adult education unit and a high school. The theoretical and methodological references of Pecheutian Discourse Analysis, as well as the models for constructing Teacher with Analogies (TWA) and the Focus-Action-Reflection (FAR) guide, were employed for data analysis. It could be inferred that the future teachers’ analogies were drawn spontaneously, while considering the analogies that students were already familiar with.
Keywords: analogies; physics teaching; science teaching; supervised internship